Vegetation Analysis of Mangrove Forest of Krishna Wildlife Sanctuary , Andhra Pradesh , India - Naithani, H. B.; Pal, R. C.; Srivastava, Rajeev K. (Indian Forester, 2004)
Paper reports on a detailed analysis of a mangrove forest of Krishna Wildlife Sanctuary , Andhra Pradesh. The study was conducted during July 2002 , and the vegetation was sampled through random sampling method. This type of study is done for the first time in Indian Context. The result shows that Avicennia officinalis , Rhizophora apiculata , Agiceras corniculatum , Bruguiera cylindrica , Ceriops decandra and Excoecaria agallocha are the common species with sufficient number of the individuals. Good regeneration of all these species were also recorded. Some areas viz. , Nachugunta beat and Machlipatnam , support sparse vegetation composed of helophyte species i.e. Suaeda nudiflora , S. monoicea , S. maritima , Salcorina brachiata , Helotropium curassavicum and grasses Aeluropus lagopoides , Sporobolus verginicus , Spinifex littoreus and Zoysia mortella. Few species of creeper Ipomoea pescarpae , herb Launea sarmentosa and hedges Cyperus arenarius and Fimbristylis polytrichoides have also been recorded. In newly formed silt deposits in inter-tidal regions , the grass Porteresia coarcata found growing as pioneer species. A pure stand of Prosopis juliflora spread over 6km area , where the seeds were brought by 1977 cyclone. In Sorlagondi beat well grown trees of Salvadora persica were also noticed.